UJI EFEK ANTIPIRETIK EKSTRAK ETANOL KULIT BATANG FALOAK (Sterculia sp.) PADA MENCIT PUTIH JANTAN (Mus musculus) YANG DIINDUKSI VAKSIN DPT-HB - NI NYOMAN YULIANI; JEFRIN SAMBARA; YASINTA SETYARINI (JURNAL INFO KESEHATAN, 2016)
One native plant Indonesia are scattered in several regions, especially in the island of Timor NTT Province and has the potential to be developed into a medicinal plant that is Faloak (Sterculia sp.) Research on the Test of Effect Antipyretic Ethanol Extract Skin Stem Faloak (Sterculia sp.) In Mice White Males ( Mus musculus) strain Swiss Webster aims to determine the antipyretic effect of the ethanol extract of the stem bark faloak and effective as an antipyretic dose in mice induced DPT-HB vaccine. Extracts prepared by maceration method using ethanol 96%. White male mice used were 20 birds and were divided into 5 groups. Each mouse induced HB DPT vaccine at a dose of 0.0013 mL / 20 g BB. The first group was given paracetamol as a positive control at a dose of 1.3 mg / 20 g BB, the second group was given Na CMC as a negative control, and the three other groups faloak stem bark ethanol extract at a dose of 150 mg/kg, 300 mg/kg BW, and 600 mg/kg. Temperature measurement is carried out for 3 hours with a 30-minute interval. Measurement data were statistically analyzed using One Way ANOVA and advanced test Post Hoc LSD showed that the ethanol extract of bark faloak with a dose of 150 mg/kg and 300 mg/kg have an activity comparable with paracetamol, while extracts of 600 mg/kg has a more optimal antipyretic activity of paracetamol at a dose of 1.3 mg / 20 g BB.